2020
DOI: 10.1016/j.annonc.2020.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing diversity in the tumor-immune microenvironment of distinct subclasses of gastroesophageal adenocarcinomas

Abstract: Background: Gastroesophageal adenocarcinomas (GEAs) are heterogeneous cancers where immune checkpoint inhibitors have robust efficacy in heavily inflamed microsatellite instability (MSI) or Epstein-Barr virus (EBV)-positive subtypes. Immune checkpoint inhibitor responses are markedly lower in diffuse/genome stable (GS) and chromosomal instable (CIN) GEAs. In contrast to EBV and MSI subtypes, the tumor microenvironment of CIN and GS GEAs have not been fully characterized to date, which limits our ability to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
103
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 33 publications
9
103
0
Order By: Relevance
“…Whether serial analysis of circulating tumor DNA could guide adaptive strategies to boost response remains to be seen. Beyond tumor genomic changes, there is a clear interplay between TME and tumor clones in GC (39,46,47). Our scRNAseq data supported clear differences in both baseline and adaptive TME composition between responders and non-responders.…”
Section: Discussionsupporting
confidence: 62%
“…Whether serial analysis of circulating tumor DNA could guide adaptive strategies to boost response remains to be seen. Beyond tumor genomic changes, there is a clear interplay between TME and tumor clones in GC (39,46,47). Our scRNAseq data supported clear differences in both baseline and adaptive TME composition between responders and non-responders.…”
Section: Discussionsupporting
confidence: 62%
“…As a vital plastic and heterogeneous population of cells in the TME, TAMs account for 30%-50% of infiltrating immune cells. 12 Circulating monocytes extravasate from nearby blood vessels and enter tumor tissue, contributing to their polarization into different phenotypes. 13 , 14 …”
Section: Tamsmentioning
confidence: 99%
“…Different histological types may differ in their ability to recruit CD8+ T cells into the TC and IF. Moreover, tumours with higher TIL infiltrates have better adaptive immune response and, thus, they respond to immune checkpoint inhibitors more effectively [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Derks et al described heterogeneity in TIME among GC molecular subtypes. In their study, chromosomal instable GCs ( n = 18) showed T cell exclusion and possessed CD8+ cells predominantly at the invasive margin [ 15 ]. We noticed a similar pattern in B7-H3-high GCs and, thus, propose that B7-H3 could be involved in this immune suppressive mechanism of TIME.…”
Section: Discussionmentioning
confidence: 99%